Effects of Brace Configuration and Structure Height on Seismic Performance of BRBFs Based on the Collapse Fragility Analysis - Hu, Jong Wan; Shokrgozar, Hamed Rahman; Golsefidi, Edris Salehi; Mansouri, Iman (Periodica Polytechnica Civil Engineering, 2020)
The brace configuration and structure height are two factors that have a significant effect on the seismic behavior of braced frame buildings. In the present study, the buckling-restrained braced (BRB) frames were considered to estimate the effect of these two parameters using probabilistic seismic assessment methods. The uncertainty in the different parameters involved in the seismic design of the structural system was also considered. Four, six, and ten-story buildings with the Chevron and inverted Chevron bracing configurations were designed, and their responses due to various ground motions were estimated using incremental nonlinear dynamic analyses. Fragility curves, mean annual frequency of exceeding immediate occupancy (IO), and collapse prevention (CP) states were generated using probabilistic seismic analysis, fragility curves concept, and drift hazard curves. The results demonstrate that the inverted Chevron type BRBFs has better structural performance than Chevron bracing types. Furthermore, an increase of the height of structures, despite lower drift’s hazards, increases the fragility probability.